MASAMBO SINGING IN TUMARATAS DUA VILLAGE, WEST LANGOWAN SUB-DISTRICT, MINAHASA DISTRICT - Resita Klaudia Alow; R.A. Dinar Sri Hartati; Luccylle Takalumang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research aims to investigate the existence and continuity of Masambo singing in Tumaratas Dua Village. Qualitative research methods were applied by utilizing documentation, interview, and observation techniques. A musical approach, particularly through theories in ethnomusicology and music psychology, was used to analyze various aspects of Masambo Singing. The research findings include several things: first, Masambo singing functions as a form of community expression, conveying prayer requests, expressions of gratitude, and as a means of communication. Second, the existence of Masambo singing provides significant benefits in maintaining cultural continuity and strengthening community solidarity. Third, the lyrics in Masambo singing are constantly changing according to the needs of the community. Fourth, the times affect the continuity of Masambo singing. Fifth, Masambo singing contains social values such as honor, mutual cooperation, deliberation, and sacrifice. Sixth, changes in Masambo singing are influenced by social, religious, cultural, and economic factors.